Strategi Pemasaran Produk Kue Mocaf di Nola Cookie, Kelurahan Pasanggrahan Baru, Sumedang Selatan - Nurjannah, Hanifah; Pardian, Pandi (Universitas Galuh, 2025)
Nola Cookie is one of the Home Industry Food in Sumedang Regency which is engaged in the processing of mocaf (modified cassava flour) based cakes. Until now, mocaf-based cake products are still not very popular, so they are not widely known and their sales are low. This study aims to formulate the most effective marketing strategy for mocaf cake products at Nola Cookie. The method used in this study is a qualitative method with a case study approach. Data were analyzed using IFAS, EFAS, SFAS, IE, SWOT, and QSPM analysis. The results of the study identified eight alternative strategies that can be implemented in marketing Nola Cookie mocaf cake products, including: 1) creating informative content about Nola Cookie mocaf cake product education, 2) taking design and digital marketing training, 3) emphasizing product safety through ownership of SPP-IRT and halal certificates in promoting products online or offline, 4) collecting consumer feedback as a requirement for claiming product discounts, 5) improving packaging design to increase product safety and product appeal, 6) creating simple promotional content around Nola Cookie activities, 7) conducting research to extend product durability and provide education to consumers on how to properly store products through social media, and 8) creating employee recruitment SOP.